DIFFUSION AND SEGREGATION PROCESSES IN HEAVY-LOADED FRICTION UNITS - Igor Vladimirovich Kolesnikov (Advanced Engineering Research, 2014)
It is stated analytically and proved experimentally that in the heavy-loaded conjugations such as a break system of the rolling stock the maximum temperature in the wheel is reached not on the surface but in the subsurface layer. The study of the non-stationary contact coupled thermoelasticity problem on the brake disk rotation, and on the experimental research of the hydrogen diffusion has shown that the design dependence type of the thermal field describes adequately the process of the hydrogen diffusion in its functional dependence on the temperature. Under these conditions, maximum of the hydrogen concentration coincides with maximum temperature. The study results on the segregation processes of the alloying and doping elements in the wheel - brake shoe tribosystem are presented. The elemental composition on the boundaries of the steel grains of the railway wheel is determined using Auger spectroscopy. The upper metal layers in the defected wheel contain iron, sulfur, phosphorus, and zinc. In the tread working layer, the sulfur and phosphorus content is much less, and it conforms to their volumetric content.